Hepatitis B-Related Decompensated Cirrhosis With Ascites Permagna In A 64-Year-Old Indonesian Farmer - Jeni Noprianti; Dessy Andriani; Paskalis Gunawan (Jurnal Ners, 2025)
Hepatic cirrhosis increased from 36.9 million in 1990 to 58.4 million in 2021. However, the burden varies significantly by etiology. In 2022, hepatitis B caused 1.1 million deaths from cirrhosis and hepatocellular carcinoma (primary liver cancer). This study highlights how important it is to understand and treat cirrhosis in hepatitis B patients as soon as it develops, as it can be fatal if not treated. We reported a case of HBV-related decompensated cirrhosis of a 64-year-old Indonesian male with a two-week history of progressive abdominal swelling that had worsened significantly in the preceding 24 hours accompanied with dyspnea and epigastric pain. Physical examination revealed bilateral icteric sclera and conjunctival pallor. Abdominal examination was remarkable for a convex, extended abdomen with weakened bowel sounds. Percussion revealed dullness in all quadrants except the umbilical region, positive fluid waves, and shifting dullness. EKG, blood laboratory, chest X-ray, and abdominal ultrasound examinations were performed. The treatment approach addresses multiple aspects of the patient's condition, including diuretics, supportive care for liver function, gastroprotection therapy, and ursodeoxycholic acid. The patient also underwent ascites puncture and found 4400 cc of serous fluid.